PENDIDIKAN MATEMATIKA REALISTIK BERBASIS BUDAYA DALAM PEMBENTUKAN KARAKTER: indonesia - Junaidi Fery Efendi (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2021)
Moral degradation of the younger generation becomes a problem for the nation, generation is the next milestone of the nation. It needs a strategy in solving this problem, one of which is the planting of character as early as possible in both primary and secondary education. Research using a realistic mathematical approach based on culture is expected to develop the character of learners. Madura traditional culture through traditional houses becomes a source of mathematics learning not only emphasizes cognitive aspects but the introduction of local culture by instilling character values. This type of descriptive quantitative research begins with interviews and documentation followed by data retrieval in the form of statistical figures using question tests and observations in students. The results showed that 85.3% of students completed their studies. Realistic mathematics makes it easier for students to understand the material by contexting real conditions, especially in traditional house buildings.